A Comparison between Pediatric and Adult Patients after Cranioplasty: Aseptic Bone Resorption Causes Earlier Revision in Children - Göttsche, Jennifer; Fritzsche, Friederike; Kammler, Gertrud; Sauvigny, Thomas; Westphal, Manfred; Regelsberger, Jan (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Background and Study Aims/Objective Cranioplasty, a common neurosurgical intervention following decompressive craniectomy (DC), is associated with high complication rates. Bone flap resorption in particular leads to a considerable number of patients requiring further surgery. The aim of this study was to investigate the frequency and time of occurrence of complications following cranioplastic procedures in children and adults.Material and Methods Data of children and adults who underwent cranioplasty between July 2010 and March 2018 were analyzed retrospectively. Clinical data, complications, and risk factors regarding aseptic bone resorption (ABR) were evaluated including patient age, occurrence of shunt-dependent hydrocephalus, and number of fragments in autologous bone flaps.Results Severe traumatic brain injury (TBI) was the leading cause for DC among children (66.7%), associated with a significantly higher number of fragments (p = 0.002). In the adult population, the most common cause was malignant infarction (55.9%) followed by TBI (24.6%). Pediatric patients in our institution received autologous bone flaps less frequently than adult patients (61.1% and 83.1%, respectively). Young age and a higher number of fragments in autologous bone flaps were associated with the occurrence of ABR. Children and adolescents showed significantly higher rates of aseptic bone necrosis (p = 0.007) and revision cranioplasty (p = 0.036). Kaplan-Meier estimates were used to further analyze bone flap resorption in children and adults, showing that revision surgery due to ABR was performed earlier in children (p = 0.001, log-rank test).Conclusion Pediatric patients demand specific care when cranioplasty is performed following DC. We identified age as an independent risk factor. The higher number of fragments appears to be a correlation due to the higher number of TBIs in children. Our data indicate that young age is the most important risk factor for the development of ABR as a frequent and early complication with a shorter revision-free time interval in children. Consequently, the uncritical use of cryopreserved autologous bone flaps should be questioned in this population.
Keywords: cranioplasty; children; adolescents; bone resorption; risk factors